The Coping Strategies of Generation X and Millennial School Principals in Managing Work-Related Stress: A Multi-Site Study at SDN Ngembe 1 and SDN Baujeng 1, Beji District - Assalamatus Sholikhah; Ahmad Thohorin; Suyitno Suyitno (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
This study aims to analyze the coping strategies of Generation X and Millennial school principals in work stress management within the context of elementary school leadership. The research uses a qualitative approach with a multi-site study design conducted at SDN Ngembe 1 and SDN Baujeng 1 in Beji District. The subjects of the study are school principals representing Generation X and Millennial, selected purposively. Data were collected through in-depth interviews, observations, and documentation, and then analyzed thematically through stages of data reduction, data presentation, and drawing conclusions, including cross-site analysis. The results show that both generations face relatively similar sources of work stress, particularly stemming from leadership role complexities, administrative demands, and stakeholder expectations. However, there are differences in how stress is perceived and managed. Generation X principals tend to use problem-solving and self-resilience-oriented coping strategies supported by work experience, while Millennial principals are more flexible, combining problem-solving, emotional management, technology utilization, and social support strategies. These findings emphasize that generational backgrounds influence the coping strategy dynamics of school principals in work stress management, which should be considered in the development of policies and programs to strengthen elementary school leadership.